Variety of Social Conflicts in Novel Drupadi Karya Seno Gumira Ajidarma - Tri Dewita; Aruna Laila; Wahyudi Rahmat (ppjbsip, 2020)
Conflict is something that cannot be avoided in social life. With the conflict, the community will be more intelligent in dealing with life and life. That is what is seen in the Drupadi novel by Seno Gumira Ajidarma. Seno Gumira Ajidarma manifests social conflict by using the uniqueness of abstract language. Social conflict is portrayed by Seno Gumira Ajidarma by asserting something with others so that the social conflict that is portrayed becomes more interesting, because it is very different in its delivery with other works. Based on then this study aims to describe the forms of social conflict and the causes of social conflict. This type of research is qualitative using the method of analysis description to explain the results of the study. The data collection technique used is descriptive literature study. The results showed that the forms and causes of social conflict were found in the form of (1) Gender conflict caused by social change, (2) Inter-group conflict caused by individual differences, (3) Conflict of interest caused by conflict of interests both in terms of economic or political, (4) Interpersonal conflicts caused by individual differences, (5) Conflicts between Social Classes, (6) Conflicts between countries / nations caused by conflicts of interests both economically or politically.